Răspuns :
3x+y=-2 l ×5
-5x-3y=2 l ×3
15x+5y= - 10
-15x-9y=6
------------------- +
/ - 4y = - 4 ⇒ y=1
3x+y=-2 l ×3
-5x-3y=2
9x+3y= - 6
-5x-3y=2
----------------- +
4x / = - 4 ⇒ x= - 1
Solutii: x= -1 si y=1
Sper ca te-am ajutat!
-5x-3y=2 l ×3
15x+5y= - 10
-15x-9y=6
------------------- +
/ - 4y = - 4 ⇒ y=1
3x+y=-2 l ×3
-5x-3y=2
9x+3y= - 6
-5x-3y=2
----------------- +
4x / = - 4 ⇒ x= - 1
Solutii: x= -1 si y=1
Sper ca te-am ajutat!
3x + y = - 2 |*3 ⇒ 9x + 3y = - 6
- 5x - 3y = 2 -5x - 3y = 2
--------------------- suma lor este ...
4x = - 4 deci: x = -1
↓
inlocuim in prima ec.
3*(-1) + y = -2
y = -2+3 = +1
y = 1
- 5x - 3y = 2 -5x - 3y = 2
--------------------- suma lor este ...
4x = - 4 deci: x = -1
↓
inlocuim in prima ec.
3*(-1) + y = -2
y = -2+3 = +1
y = 1